2013
DOI: 10.1128/jvi.02906-12
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD151 Mediates Papillomavirus Type 16 Endocytosis

Abstract: cHuman papillomavirus type 16 (HPV16) is the primary etiologic agent for cervical cancer. The infectious entry of HPV16 into cells occurs via a so-far poorly characterized clathrin-and caveolin-independent endocytic pathway, which involves tetraspanin proteins and actin. In this study, we investigated the specific role of the tetraspanin CD151 in the early steps of HPV16 infection. We show that surface-bound HPV16 moves together with CD151 within the plane of the membrane before they cointernalize into endosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
171
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(181 citation statements)
references
References 73 publications
(100 reference statements)
7
171
0
Order By: Relevance
“…For example, CD81 and TSPAN9 have been recently identified in genome-wide small interfering (si)RNA screens for host factors that regulate the early steps of influenza virus and Alphavirus infection, respectively (Karlas et al, 2010;Kö nig et al, 2010;Ooi et al, 2013); it has also been suggested that CD81 and TSPAN9 regulate viral fusion in endosomes (He et al, 2013;Ooi et al, 2013). CD151 has been shown to contribute to the endocytosis of the human papillomavirus (HPV)16, an etiologic agent for cervical cancers (Scheffer et al, 2013). This function of CD151 requires an interaction with integrins (integrin a6 has previously been identified as a receptor for HPV) and its palmitoylation (and so presumably interaction with other tetraspanins).…”
Section: Box 1 Tetraspanins In Infectious Diseasesmentioning
confidence: 99%
“…For example, CD81 and TSPAN9 have been recently identified in genome-wide small interfering (si)RNA screens for host factors that regulate the early steps of influenza virus and Alphavirus infection, respectively (Karlas et al, 2010;Kö nig et al, 2010;Ooi et al, 2013); it has also been suggested that CD81 and TSPAN9 regulate viral fusion in endosomes (He et al, 2013;Ooi et al, 2013). CD151 has been shown to contribute to the endocytosis of the human papillomavirus (HPV)16, an etiologic agent for cervical cancers (Scheffer et al, 2013). This function of CD151 requires an interaction with integrins (integrin a6 has previously been identified as a receptor for HPV) and its palmitoylation (and so presumably interaction with other tetraspanins).…”
Section: Box 1 Tetraspanins In Infectious Diseasesmentioning
confidence: 99%
“…Endocytosis of viral particles is mediated by a clathrin-, dynamin-, and caveolin-independent mechanism but requires tetraspanin CD151 and the actin cytoskeleton (10,27,28,(31)(32)(33)(34). Following internalization, viral particles are found in CD63-positive endosomes recruiting syntenin-1, a CD63-interacting adaptor protein (35).…”
mentioning
confidence: 99%
“…Furin cleavage may also occur during virion morphogenesis, as shown for tissue-derived native HPV16, resulting in infection independent of cellular furin (25). The precleaved virus is transferred to tetraspanin-enriched microdomains (TEMs) (27,28), where L2 directly interacts with the annexin A2 heterotetramer (A2t), a protein localized on the outer and inner leaflet of the plasma membrane and mediating viral endocytosis and infection (29,30). Interaction occurs be- Citation Wüstenhagen E, Hampe L, Boukhallouk F, Schneider MA, Spoden GA, Negwer I, Koynov K, Kast WM, Florin L. 2016.…”
mentioning
confidence: 99%
“…Following primary attachment and internalization, acidification of early endosomes triggers capsid disassembly (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Host cell cyclophilins release the majority of L1 from the L2 protein, which remains in complex with the viral genome (2,23,24).…”
mentioning
confidence: 99%